Joint effect of urinary arsenic species and serum one-carbon metabolism nutrients on gestational diabetes mellitus: A cross-sectional study of Chinese pregnant women. (November 2021) - Zhang, Qiang; Zhang, Xumei; Li, Shuying; Liu, Huihuan; Liu, Liangpo; Huang, Qingyu; Hou, Yaxing; Liang, Xiaoshan; Cui, Bo; Zhang, Ming; Xia, Liting; Zhang, Liwen; et al.
Highlights: Arsenite (As 3+ ) is positively associated with GDM. Arsenate (As 5+ ) shows a negative relationship with GDM. Synergistic effects are found between arsenic and vitamin B12 on GDM. Abstract: Background: Growing evidence indicates that arsenic (As) exposure can increase the risk of gestational diabetes mellitus (GDM). However, little is known about As species and GDM and the combined effect of As and one-carbon metabolism (OCM) on GDM. Objectives: We aimed to examine the associations between As species and GDM and evaluate the potential interactions of folate, vitamin B12, and homocysteine (Hcy) with As species on GDM prevalence. Method: We measured levels of arsenite (As 3+ ), arsenate (As 5+ ), dimethylarsinic acid (DMA), and arsenobetaine (AsB) species in urine and folate, vitamin B12, and Hcy in serum from 396 pregnant women in Tianjin, China. The diagnosis of GDM was based on an oral glucose tolerance test. Associations of As species in urine with GDM were evaluated using generalized linear models (GLMs) and Bayesian kernel machine regression (BKMR). Additive interactions of As and OCM with GDM were estimated by determining the relative excess risk due to interaction (RERI). Results: Of the 396 pregnant women, 89 were diagnosed with GDM. Continuous increases in urinary inorganic As were associated with GDM in the GLMs, with adjusted odds ratios of 2.12 (95% CI: 0.96, 4.71) for As 3+, and 0.27 (95% CI: 0.07, 0.98) for As 5+ . The BKMR in estimating the exposure-response functions showed that As 3+ and AsB were positively associated with GDM. However, As 5+ showed a negative relationship with GDM. Although the additive interactions between As exposure and OCM indicators were not significant, we found that pregnant women with higher urinary As 3+ and total As accompanied by lower serum vitamin B12 were more likely to have higher odds of GDM (3.12, 95% CI: 1.32, 7.38 and 3.10, 95% CI: 1.30, 7.38, respectively). Conclusions: Our data suggest a positive relation between As 3+ and GDM but a negative relation between As 5+ and GDM. Potential additive interaction of As and OCM with GDM requires further investigation.